Men, masculinities and honour-based abuse - Idriss, Mohammad Mazher (A GlassHouse book, 2020)
"This book explores the largely neglected relationship between men, masculinities and honour-based abuse (HBA). There is a common misconception that HBA - whether physical violence, emotional abuse or so-called 'honour' killings - occurs only against women. This book addresses the gap in the current literature concerning the relationship between men, masculinities and HBA. With contributions from an international and interdisciplinary range of both academics and professionals, the book examines HBA and forced marriages specifically from male-victim perspectives, both in the UK and internationally. Providing a clear understanding of the main theoretical and sociological explanations of HBA against male victims, the book demonstrates that, although men are indeed the main perpetrators of HBA, state agencies must address the fact that many men are also victims. This book is essential reading for students, academics, and practitioners alike"--